Assessment of the clinical outcomes and patient satisfaction when using bilateral radial artery as surgical conduits in coronary artery bypass grafting - Wayel S Bebawy; Ashraf Abd-Elaziz; Emmanuel Louka Aziz (Journal of Medicine in Scientific Research, 2022)
Introduction The need for use of the bilateral radial artery has emerged since we faced patients in our institute with severe uncontrolled diabetes, bilateral leg elephantiasis, and left main disease that needs surgical revascularization. Patients and methods We reviewed the outcomes from our institute with retrospective analysis of prospectively collected clinical data from our local clinical database and identified 30 consecutive patients who underwent coronary artery revascularization requiring the use of bilateral radial harvest. Patient satisfaction was assessed using a quality-of-life questionnaire with the descriptors on a Likert Scale (table A). The patients were followed up both clinically and by ECG and echocardiography every 6 months for 2 years postoperatively to follow up their ejection fraction and for the assessment of any new segmental wall motion abnormalities. Results Only three (12.5%) patients out of 24 reported 'rarely' or sometimes arm pain or discomfort, while all the others (87.5%) were asymptomatic. The median score for arm and sensory and neurological complications was 5. Three (12.5%) patients reported long-term permanent sensory deficit, while six (25%) patients had some other less-significant sensory loss. Only one (4.2%) patient reported significant motor dysfunction, while five (20.8%) patients reported milder forms of motor deficit. Thirteen (54.1%) patients considered the appearance of radial harvest site as excellent, while 23 (95.8%) patients considered it to be at least acceptable. One (4.2%) patient reported a 'moderate' functional change otherwise, the remaining patients reported 'minimal' (12.5%) or 'no change' (83%). The functional outcomes from our series of patients remain favorable with minimal functional decline in the majority of our patients. Both clinical ECG and echocardiographic follow-up revealed stability of all followed patients without the need for CCU admission or repeat revascularization in this time period. Conclusions Using bilateral radial artery as surgical conduits in coronary artery bypass grafting is acceptable to patients when alternatives are not favorable for surgical revascularization.